PENGEMBANGAN MEDIA FLIPBOOK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI SISTEM EKSKRESI MANUSIA - Shanti Yuniar Rahmawati; Aris Singgih Budiarso; Sri Wahyuni (ScienceEdu, 2024)
Learning media conveys information between teachers and students to create an effective and efficient learning environment. The media delivery method used by the teacher can make students more accepting and understanding of the information appropriately obtained. Based on a survey conducted by PISA, science learning achievement in Indonesia is low. Ranking in the top 10 bottom can affect students' critical thinking because they need help applying their problem-solving knowledge correctly. One alternative to improve students' critical thinking skills is to make learning more interactive so that students' critical thinking skills can increase. Flipbook media expect to stimulate and enhance students' critical thinking skills. If students have mastered critical thinking skills, they can combine the knowledge they have acquired and express this knowledge.This study aimed to describe flipbook media that is valid, practical, and effective in improving students' critical thinking skills. The ADDIE development model is used as a research design because it has a systematic method and widely uses as a development model related to media production. The ADDIE stages start from analysis, design, development, implementation, and evaluation. Data collection techniques used in this study include validation methods, tests, and questionnaires. The instruments used were media validity sheets, materials, and questionnaires in the form of student responses after using flipbook media. Based on the research results, the developed flipbook media included valid, practical, and effective media for learning.